BUTTERFLIES RECENTLY RECORDED FROM LOMBOK - Kazuma Matsumoto; Woro A Noerdjito; Endang Cholik (Treubia, 2012)
Ten species of butterflies were recently recorded from Lombok, i.e., Papilio demoleus malayanus, Appias olferna, Eurema andersoni kashiwaii, Theclinesthes miskini gaura, Tirumala ishmoides linea, Acraea andromacha, Acraea terpsicore, Junonia villida, Lexias aegle miyatai and Mycalesis mineus macromalayana. Papilio demoleus malayanus, A. olferna and A. terpsicore were thought to be recent immigrants from the mainland Asia, and likewise J. villida from Australia. We could not determine whether A. andromacha, recorded by only one specimen, is a native species or a stray from Sumbawa. The other species were supposed to be native to Lombok.